SINTESIS KEMOSENSOR ION CN- BERBASIS TURUNAN PIRAZOLIN DENGAN LOGAM Cu - Yulian Syahputri; Diah Indah Purwati; Sutanto Sutanto; Agus Taufiq (Universitas Pakuan, 2021)
One of the toxic anions such as cyanide (CN-) has a negative impact on living things. Pyrazoline derivatives can be complexed with transition metals and used as CN- ion fluorosensor, because pyrazoline derivatives have fluorescence properties. This study aims to synthesize of CN- ion chemosensors based on pyrazoline derivative namely para-di-2-(1-phenyl-3-pyridyl-4,5-dihydro-1H-pyrazole-5-yl)benzene with Cu metal. The resulting complex compounds were characterized using Spectrophotometer Infra Red (FTIR), Spectrophotometer UV-Visible, and Spectrofluorometer. Then, a complex compound chemosensor (fluorosensor) study of Cu2+ was carried out with the addition of CN- ions using a spectrofluorometer. The results showed that the synthesis of complex compound Cu2+ was successfully carried out and a brown precipitate was obtained with a yield of 43% with a melting point of 243.3Â°C. Based on the results of characterization by FTIR (cm-1) generates 3400 (Amine), 2920.88-2852.42 (C-H pyridine), 2360.38 (C=N), 1594.50-1490.39 (C=C aromatic), 1233.67-1021.17 (C-N), Â 982.66 (Cu-O), 348.00 (Cu-N), and 320-280 (Cu-Cl). The results of the spectroscopy UV-Visible analysis Cu2+ complex compounds at a concentration of 5x10-5 M obtained two absorption peaks, 242 nm and 306 nm. The result of the spectrofluorometer analysis of Cu2+ complex compound were 1516 a.u at a wavelength of 502 nm. The results of the chemosensor (fluorosensor) studies of the Cu2+ complex compound with the addition of CN- ions can be used as a turn on-off Â type fluorosensor.